Application of Chitosan Coating for Quail (Coturnix Coturnix) Egg Preservation - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Quails are becoming more popular as a source of meat and egg because of their small body size, rapid generation turnover and high egg production. Quail eggs are the good source of nutrients for human health, being one of the best and most economical sources of high quality protein. Although quail eggs are small in size, their nutritional value is three to four times greater than chicken eggs and is packed with vitamins and minerals. Quail eggs are becoming more and more popular as they fulfill the criteria of a product with traits of functional food. Objective of this research focused on the effect of different chitosan concentrations (0%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%), effect of storage temperature condition (4oC, 28oC) to quail egg quality. Results showed that coating 2.5% of chitosan and preserving at 4oC could extend quail egg quality for 60 days.Keywords: Quai egg, Coating, Chitosan, Concentration, Temperature, Preservation.